Formulation and acceptability studies of rough lemon (Citrus jambhiri Lush.) squash. (Indian Journal of Arid Horticulture, 2025)
Rough lemon fruits are highly acidic and possess greater nutraceutical value. Studies were conducted to formulate and assess the acceptability of squash from rough lemon. The varying juice concentrations (50%, 40%, 30%, 20%, and 10%) were used for preparing the squash and stored at ambient temperature (28 ± 3°C). Periodic observations were recorded at fresh (0), 3, and 6-month intervals. Squash prepared with 40% juice was found to be the best recipe with respect to organoleptic qualities, such as color, flavor, taste, and overall acceptability, even after 180 days of storage under ambient conditions.